Pengembangan Sumber Daya Insani Di Lembaga Keuangan Islam - Mohammad Afif (Universitas Islam Lamongan, 2016)
Islamic financial institutions began to flourish in Indonesia. Naturally there is a demand for creating human resources with good morality and professional in carrying out its duty, mission and vision. Talking about human resources, in fact, we can see from two aspects, namely the quantity and quality. Islamic financial institution requires two aspects. Islamic financial institutions will exist when supported by adequate human resources for the development, which is actually Indonesian with the biggest Muslim country of in the world, so that the market share for Islamic financial Institution is very potential. Therefore, it is ironic if the Islamic financial institution can not flourish in Indonesia. It is necessary for strategic steps in the establishment of the Islamic financial Institutions. Thus, Islamic character of this vision is a solution that is a manifestation of human nature as a creature of Allah, who is in every movement and steps always use the rules set by Allah. The occurrence of fraud by operators of Islamic financial institutions because he is out of the nature of faith and choose the wrong path. So it is important for a leader being model, to pay attention, oversee, audit and punish managers who disapprove his nature, both in financial terms and non financial problems. Founder, trustees, managers may commit violation because of unlimited power, due to excessive power. Excessive confidence sometimes opens human opportunities to get out of the nature of faith. This article will try to explain the development of human resources in Islamic financial institutions, which includes the importance of human resources planning, the principles of employees planning in Islamic financial institutions, the process of human resources planning in Islamic financial institutions, the values of recruitment, the stages of recruitment, the technique of potential seeking in recruitment, and so forth. Keywords: Islamic financial institution, Human resources